2020
DOI: 10.1111/ggr.12370
|View full text |Cite
|
Sign up to set email alerts
|

Geostandards and Geoanalytical Research Bibliographic Review 2019

Abstract: This bibliographic review gives an outline of publications in 2019 focusing on reference materials (RMs) used in geochemistry and related fields, such as palaeoclimate and environmental research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The annual Geostandards and Geoanalytical Research bibliographic review (over 600 references) provided 216 an overview of papers published in 2020 that contributed important data for geoanalytical RMs. A substantial number of the publications focused on newly developed RMs and analytical data for existing RMs obtained using improved methods.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
“…The annual Geostandards and Geoanalytical Research bibliographic review (over 600 references) provided 216 an overview of papers published in 2020 that contributed important data for geoanalytical RMs. A substantial number of the publications focused on newly developed RMs and analytical data for existing RMs obtained using improved methods.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
“…An annual bibliographic survey provided 198 a summary of RMs used in geochemistry and related fields , such as paleoclimate and environmental research, that featured in papers published in 2019. This review examined 6850 papers from more than 20 scientific journals and used data from nearly 700 articles.…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%
“…A study conducted by Weis et al [9] revealed that out of 7200 analytical geochemistry publications, only 9% presented the measurement of the results for certified reference materials (CRMs) which provide traceability. This means that the vast majority of the results that are being currently published are not validated, which is not a healthy situation.…”
Section: Major Factors Responsible For the General Decline In Quality...mentioning
confidence: 99%